Factors Associated with Delays in Services for General Policy Outpatient Patients at The Registration Lock of The Nuhon Health Center, Banggai District Year 2023 - Desi Novitasari (Westscience Press, 2024)
Delays in patient services are generally often found in health facilities, both hospitals and community health centers. One of the community health centers in Banggai Regency which still often experiences problems with delays in patient service is the Nuhon Community Health Center. This health center, which is located in the Nuhon District area, serves outpatients in several polyclinics, one of which is the general polyclinic. One of the hopes of patients when visiting health facilities is that they don't have to wait long to get service, but there are still many statements from patients who complain about delays in service at the registration counter. This study aims to determine the factors associated with delays in general poly outpatient services at the Public Health Center Registration CounterNuhon, Nuhon District, Banggai Regency in 2023. This research is an analytical survey research with a type approachcross-sectional, by taking samples by accidental sampling with a total sample of 130 people. The statistical test used is Chi square to see the relationship between service delays and the performance of registration counter staff and facilities. The results of this study indicate that there is a relationship between the performance of the registration counter staff, facilities and delays in providing services to general poly outpatients at the Nohon Health Center Registration Counter, Nuhon District, Banggai Regency and the value of health workers isp =0.000 while the means have a relationship with a value of p = 0.000. Therefore, it is necessary to improve the performance of health workers and provide supporting facilities in the health service process.